PORTFOLIO OPTIMAL ANALYSIS: SIMPLE CAPM TESTING, COMPARING BENCHMARK PERFORMANCE TO MUTUAL FUNDS (EQUITY AND MIXED), AND COMPARING PORTFOLIOS PERFORMANCE THROUGH EX-POST AND BLACK-LITTERMAN MODEL ILLUSTRATION (A Case Study on Public Companies listed in Indonesia Stock Exchange and 53 mutual funds (equity and mixed) managed in 2010 – 2014) - Basuki, Abdullah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study deals with